COMMUNICATION POLICIES REFLECTION ON GLOBALIZATION PROCESS AND THE ROLE OF ADVERTİSEMENT IN INTEGRATED COMMUNICATION ENVIRONMENT - Abdullah Özkan (Erciyes University, 2013)
Globalization process has created important changes and transformations across the world. These political, social, economic and cultural changes have considerably affected communication. The number of mass media instruments have increased, informatics has improved and also reaching information has become easier after the globalization of communication. New communication instruments and environments have been created. Globalised communication has also affected people, reaching the information has become easier for them. Furthermore, they have much more options. Meanwhile, by this developments it has become more difficult to convince people compared to before. In a period that communication instruments have been varied and convincing has become more difficult, a new approach called as “Integrated Marketing Communication” is discussed. In this study, the conditions creating Integrated Marketing Communication and reasons for preference are analyzed. The new role of advertising in Integrated Communication Environment is discussed.